Evolutionary tendencies of implementing the notion of time in the English language and discourse - Bondarenko, Y. V. (Cognition, Communication, Discourse, 2018)
This article addresses the issue of cognitive and semantic characteristics of the lexical means of verbalizing the notion of time as a scientific and non-scientific phenomenon in the system of the English language and in different types of discourse in the 7th- 21st centuries. Duality of the notion of time is conditioned by two diffuse types of world perception, the scientific and non-scientific ones, which are manifest in the ‘cold’ and ‘warm’ world images respectively. Projection of the notion of time into the language and discourse is described with the help of the time model. The time model in the system of the English language is considered as a domain matrix which serves as a cognitive underpinning for the lexical/semantic field of time. The time model in discourse is presented as a domain matrix to describe the relationships of the basic TIME domain with other domains.